An investigation of scapular dyskinesis in recreational surfers and non-surfers - C. Re; D. Schmidt; E. Quartini; E. Dale; S.C. Newcomer; J. Furness; J.A. Nessler (Elsevier, 2023)
Summary: Recreational surfers frequently present with shoulder injuries yet there has been little research into factors that might increase injury risk in this population. Objectives: The purpose of this study was to compare the presence of scapular dyskinesis in a group of surfers and non-surfers. Design: Cross-sectional. Methods: A total of 215 participants (108 surfers, 107 non-surfers) were video recorded while performing unweighted, bilateral shoulder flexion and abduction. Videos were assessed by three clinicians to evaluate scapular dyskinesis. Participants were grouped along several different variables including age, sex, participation in other overhead sports, pain, dominant arm, injury history, skill level, surf experience, and the percent of participants exhibiting scapular dyskinesis was calculated for each category. Results: Surfers and non-surfers both presented with 48% positive scapular dyskinesis tests (OR ​= ​1.018, 95% CI: 0.596-1.738). No significant differences were detected among groups divided along any of the variables analyzed. Percentage of agreement between clinicians was 72% (Fleiss' kappa = 0.46). Conclusions: These findings suggest that recreational participation in the sport of surfing has a minimal impact on the likelihood of exhibiting scapular dyskinesis. The interrater reliability of an assessment protocol using video recordings was fair to moderate.